A Single Centre Experience of First "One Hundred Laparoscopic Liver Resections". (11th February 2014) - Rehman, S.; John, S. K. P.; French, J. J.; Manas, D. M.; White, S. A.
Abstract : Background . Laparoscopic liver resection (LLR) has emerged as an alternative procedure to open liver resection in selected patients. The purpose of this study was to describe our initial experience of 100 patients undergoing LLR. Methods . We analysed a prospectively maintained hepatobiliary database of 100 patients who underwent LLR between August 2007 and August 2012. Clinicopathological data were reviewed to evaluate surgical outcomes following LLR. Results . The median age was 64 and median BMI 27. Patients had a liver resection for either malignant lesions (n = 74 ) or benign lesions (n = 26 ). Commonly performed procedures were segmentectomy/metastectomy (n = 55 ), left lateral sectionectomy (LLS) (n = 26 ), or major hepatectomy (n = 19 ). Complete LLR was performed in 84 patients, 9 were converted to open and 7 hand-assisted. The most common indications were CRLM (n = 62 ), followed by hepatic adenoma (n = 9 ) or hepatocellular carcinoma (n = 7 ). The median operating time was 240 minutes and median blood loss was 250 mL. Major postoperative complications occurred in 9 patients. The median length of stay (LOS) was 5 days. One patient died within 30 days of liver resection. Conclusions . LLR is a safe and oncologically feasible procedure with comparable short-term perioperative outcomes to the open approach. However, further studies are necessary to determine long-term oncological outcomes.